Feasibility analysis and optimization design of PMSM with 120° phase belts toroidal windings for electric vehicles - Si, Jikai; Gao, Mengzhen; Yang, Xiangyu; Gao, Caixia; Feng, Haichao; Hu, Yihua (IET electric power applications, 2021)
A permanent magnet synchronous motor (PMSM) is introduced with 120° phase belts toroidal windings (PBTWs) (120°PBTWPMSM), in which its armature reaction field principle is elaborated. Then, the experiment concerning the 120°PBTWPMSM is conducted to verify the validity of the related analysis and the feasibility of the 120°PBTWPMSM. In addition, a method of shifting the magnetic poles (SMP) is adopted to suppress the cogging torque and the torque ripple. After this, the 120°PBTWPMSM after SMP is further optimised by the Taguchi method to obtain the structural parameters of the motor with optimal comprehensive performance. Finally, the performance of the original motor, the 120°PBTWPMSM after SMP and the optimal motor are compared, which verify the effectiveness of the optimization methods.